Institutional dynamics of regulatory actors in the recruitment of migrant workers : the case of Indonesia - Karim, Moch Faisal (Asian Journal of Social Science, 2017)
This paper examines how institutional dynamics among regulatory institutions affect the governance of the recruitment of Indonesian low-skilled migrant workers. Two institutional reforms have been made to create better governance for Indonesian migrant workers in the post-authoritarian era. One was the establishment of the National Agency for the Placement and Protection of Indonesian Migrant Workers (BNP2TKI) while the other was the granting of greater responsibility to sub-national governments to supervise migrant worker recruitment. In spite of these institutional reforms, little progress has been made in the protection of Indonesian migrant workers. The paper reveals that the restrictive regulatory framework for the recruitment of migrant workers, which curbs private recruitment agencies, does not create better migrant worker governance. This regulatory framework does not take into consideration the horizontal relationship between the old and new institutions, and the vertical relationship between the central and sub-national governments. Horizontally, the institutional design of the proposed new regulatory framework has created institutional rivalry between the newly established regulatory actor and the old one. Vertically, the reluctance of central government to decentralise authority to sub-national governments has curtailed the ability of sub-national governments to perform a supervisory role in the recruitment process. These two inter-related factors have hindered the efforts to create a better recruitment process for Indonesian migrant workers.